Interplay of soil characteristics and arbuscular mycorrhizal fungi diversity in alpine wetland restoration and carbon stabilization - Tang, Hao; Li, Qian; Bao, Qian; Tang, Biao; Li, Kun; Ding, Yang; Luo, Xiaojuan; Zeng, Qiushu; Liu, Size; Shu, Xiangyang; Liu, Weijia; Du, Lei (Frontiers in Microbiology, 2024)
Alpine wetlands are critical ecosystems for global carbon (C) cycling and climate change mitigation. Ecological restoration projects for alpine grazing wetlands are urgently needed, especially due to their critical role as carbon (C) sinks.However, the fate of the C pool in alpine wetlands after restoration from grazing remains unclear. In this study, soil samples from both grazed and restored wetlands in Zoige (near Hongyuan County, Sichuan Province, China) were collected to analyze soil organic carbon (SOC) fractions, arbuscular mycorrhizal fungi (AMF), soil properties, and plant biomass. Moreover, the Tea Bag Index (TBI) was applied to assess the initial decomposition rate (k) and stabilization factor (S), providing a novel perspective on SOC dynamics. The results of this research revealed that the mineral-associated organic carbon (MAOC) was 1.40 times higher in restored sites compared to grazed sites, although no significant difference in particulate organic carbon (POC) was detected between the two site types. Furthermore, the increased MAOC after restoration exhibited a significant positive correlation with various parameters including S, C and N content, aboveground biomass, WSOC, AMF diversity, and NH4 + . This indicates that restoration significantly increases plant primary production, litter turnover, soil characteristics, and AMF diversity, thereby enhancing the carbon stabilization capacity of alpine wetland soils.